Pacotilhando: Abolição, pós emancipação e libertos no Maranhão (1888 - 1908) - SANTOS, Carlos André Colins dos (2021)
Slavery was legally justified during the colonial period and most of the Brazilian Empire, as well, created narratives and stories about the enslaved. The long duration of the mode of production and exploitation of black men dispossessed of their own land and the constant conflicts with their masters caused international pressure, as a result of the political and economic transformations that the world had experienced. Likewise, the demands of a market that no longer considered the black subject as a product, but as a consumer, pressed for necessary changes in slave relations in the world and, specifically, in Brazil. Therefore, we seek to understand, as a research proposal, the representations of generations of freedmen in the Maranhão press (Journal Pacotilha) during the period from 1888 to 1908. Three moments are essential in the construction of this academic enterprise. 1). Understand the issue of the genesis and formation of the press in Maranhão, considering the different historical and social moments in the production of writing. two). To apprehend the period of the abolition of slavery from the Lei Áurea in the imagination of the protagonists of the newspaper Pacotilha, focusing on the region of São Luís. 3). Finally, we will seek to analyze the representations of the term freed in the newspaper Pacotilha. Therefore, we consider that in the post-abolition period the term freed not only gained different meanings but also created mechanisms to incubate certain slavery practices still present in the reality of black men and women in Maranhão society.